Discovery of 4-ethoxy-7H-pyrrolo[2, 3-d]pyrimidin-2-amines as potent, selective and orally bioavailable LRRK2 inhibitors. Issue 9 (15th May 2018) - Ding, Xiao; Stasi, Luigi Piero; Ho, Ming-Hsun; Zhao, Baowei; Wang, Hailong; Long, Kai; Xu, Qiongfeng; Sang, Yingxia; Sun, Changhui; Hu, Huan; Yu, Haihua; Wan, Zehong; et al.
Graphical abstract: Abstract: Inhibition of LRRK2 kinase activity with small molecules has emerged as a potential novel therapeutic treatment for Parkinson's disease. Herein we disclose the discovery of a 4-ethoxy-7 H -pyrrolo[2, 3- d ]pyrimidin-2-amine series as potent LRRK2 inhibitors identified through a kinase-focused set screening. Optimization of the physicochemical properties and kinase selectivity led to the discovery of compound7, which exhibited potent in vitro inhibition of LRRK2 kinase activity, good physicochemical properties and kinase selectivity across the kinome. Moreover, compound7 was able to penetrate into the CNS, and in vivo pharmacology studies revealed significant inhibition of Ser935 phosphorylation in the brain of both rats (30 and 100 mg/kg) and mice (45 mg/kg) following oral administration.